2013
DOI: 10.1007/s11033-013-2736-7
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding genes implicated in response to stripe rust pathogen stress in wheat (Triticum aestivum L.)

Abstract: The non-protein-coding genes have been reported as a critical control role in the regulation of gene expression in abiotic stress. We previously identified four expressed sequence tags numbered S18 (EL773024), S73 (EL773035), S106 (EL773041) and S108 (EL773042) from a SSH-cDNA library of bread wheat Shaanmai 139 infected with Puccinia striiformis f. sp. tritici (Pst). Here, we isolated four cDNA clones and referred them as TalncRNA18, TalncRNA73, TalncRNA106 and TalncRNA108 (GenBank: KC549675-KC549678). These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…Many of these potential lncRNAs shared structural similarities to known lncRNAs, and they clearly differed from protein-coding genes and non-transcribed regions in their sequence composition as well as in potential secondary structure [15]. Based on expressed sequence tag (EST) databases of wheat infected by Puccinia striiformis (Pst), three lincRNAs and one lncNAT cDNAs were isolated and shown to be differentially expressed in three near-isogenic lines after Pst inoculation, suggesting their participation in pathogen-defense responses [16].…”
Section: Hunting Lncrnas In Plant Genomesmentioning
confidence: 99%
“…Many of these potential lncRNAs shared structural similarities to known lncRNAs, and they clearly differed from protein-coding genes and non-transcribed regions in their sequence composition as well as in potential secondary structure [15]. Based on expressed sequence tag (EST) databases of wheat infected by Puccinia striiformis (Pst), three lincRNAs and one lncNAT cDNAs were isolated and shown to be differentially expressed in three near-isogenic lines after Pst inoculation, suggesting their participation in pathogen-defense responses [16].…”
Section: Hunting Lncrnas In Plant Genomesmentioning
confidence: 99%
“…In studies on plant–pathogen interactions, the expression levels of four lncRNAs from wheat Triticum aestivum L. have been shown to change differentially upon inoculation with Puccinia striiformis f. sp. Tritici (Zhang et al ., ). In tomato–TYLCV interaction, it was found that tomato lncRNA Slylnc0195 might function as a competing endogenous RNA by biding to miR166 via target mimicry to protect its targets, class III HD‐Zip transcription factor genes (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Target mimics, also described as miRNA decoys, sponges or competing endogenous RNAs (ceRNAs), are generally belonged to long non-coding RNA (lncRNA) class [8]. LncRNAs are RNA transcripts that are longer than 200 nt in length and lack open reading frame [9].…”
Section: Introductionmentioning
confidence: 99%